STUDENTS’ PROBLEMS AND MOTIVATIONS TO CONTINUING STUDY AT THE ENGLISH EDUCATION OF MAGISTER PROGRAM IN MAKASSAR - Muhammad Astrianto Setiadi; Reskyani Reskyani; Sahril Sahril (Universitas Muhammadiyah Makassar, 2022)
This research aims to find out the problems and also the motivations of students experience or face when they want to continue their studies in the English education of magister program at the State University of Makassar. In this study, the researchers used a method in which the method was a descriptive qualitative method. Meanwhile, the researchers conducted this research in the English Education magister program at the State University of Makassar. Then the respondents in this study totaled 30 students, they were students in the fourth semester English education program. The data in this study were taken directly from the sample by the researchers using several questions where the questions were open-ended questions given by the researchers to the respondent. Then the data were transcribed and analyzed by the researchers.The findings in this study were based on research problems students’ problems and motivations to continue studying at the English education of master program at the State University of Makassar, namely 1) The researchers found that there were six problems faced by students while they were learning English of magister program in State University of Makassar. The problems were: 1. The problem of student academics, 2. Student administrative problems, 3. Student problems with their lecturers, 4. Student financial problems, 5. Student time management problems, and also 6. Student facility problems, 2) the researchers also found 5 types of motivational backgrounds of students in continuing their studies in the English education of the magister program, and the types were: 1. Student quality motivation, 2. Student career motivation, 3. Student economic motivation, 4. Student social motivation and finally 5. Motivation is based on their family.